Erotyka pieniądza - Faulstich, Werner (Wydawnictwo Naukowe UAM, 2013)
Money, which is a phenomenon of the economic system, can be perceived from the perspective of eroticism, which is a phenomenon that is embedded in the interpersonal system. Eroticism is based on a drive and it means some particular attraction or inclination to someone. The following questions arise then: What kind of attraction is it? How should this inclination be understood? Eroticism entails the convergence of desire and a promise, which can only be captured from the perspective of cultural studies, i.e. by situating money in a cultural system. The eroticism of money is an attractive topic as its meaning goes beyond the boundaries of a system and society, which is why also those who are not competent in the field of economics can take a stance with regard to this matter. The cultural aspect of money has been discussed occasionally so far. As for cultural studies, the analysis of money mostly entails two approaches: historical and critical. This is because one should analyze the issue of money from the historical perspective while keeping a critical distance and not being afraid of making evaluations.
Eroticism of money